Engineering of Co/Co3O4 core/shell nano-heterostructures for high performance supercapacitor electrodes. (2022) - Kumari, Sumi; Bhatia, Deepak
Abstract: This study demonstrates a scheme to design and fabricate a novel core/shell Co/Co3O4 nano-architecture electrode for supercapacitor with significantly improved capacitive performance through hydrogenation. The specific capacitance of the as prepared 1D core/shell Co/Co3 O4 nano-heterostructure (∼2010 F g −1 at 2.5 A g −1 ). The improved pseudocapacitive properties of hydrogenated Co/Co3 O4 nano-heterostructures are attributed to the incorporation of the hydroxyl groups on the Co3 O4 surface due to hydrogenation, where the metallic Co nanowire core of this unique core/shell nano-heterostructure serves as the efficient channel for the fast electron conduction to the current collector. The Co/Co3 O4 nano-heterostructures exhibit good rate capability (retain nearly 60% of its initial charge) and good long-term cycling stability with excellent specific energy and power densities of 22 Wh kg −1 and 5.6 kW kg −1, respectively, at a current density of 21 A g −1 . This study demonstrates that the Co/Co 3 O 4 nano-heterostructures is very promising for next generation high-performance electrode for supercapacitor.